Thirteen simple lifestyle scores and risk of cancer, cardiovascular disease, diabetes, and mortality: prospective cohort study in the UK Biobank - Ding, Jie; Schöttker, Ben; Brenner, Hermann; Hoffmeister, Michael (International journal of cancer, 2025)
Numerous simple lifestyle scores have been developed for specific non-communicable diseases (NCDs). This research aimed to investigate and compare the associations of various lifestyle scores with the incidence and mortality of NCDs. In 76,399 participants from the UK Biobank, we investigated the associations of 13 lifestyle scores with the incidence and mortality of cancer, cardiovascular disease (CVD), type 2 diabetes (T2D), and a composite of these NCDs. Cox proportional-hazards regression models were used to estimate hazard ratios (HRs) for associations between lifestyle scores and NCD outcomes. During a median follow-up time of 10.5 years, 12,214 incident NCD cases and 2250 NCD deaths were documented. Higher lifestyle scores were generally associated with a reduced risk of overall NCDs (HRs ranging from 0.65 to 0.89) and NCD mortality (0.51-0.92). Cancer (HRs ranging from 0.72 to 0.98) and CVD (0.55-0.87) risk were less dependent on lifestyle behaviors than T2D (0.18-0.74). Notably, the top three scores associated with cancer outcomes included smoking as a component, and those for T2D included body mass index (BMI). For overall NCD outcomes, lifestyle scores including both smoking and BMI showed the strongest associations. Healthy Lifestyle Score and the Chronic Disease Risk Index were the overall best-performing scores to predict NCD risk and mortality. These findings suggest that the use of lifestyle scores designed for a single disease group can be extended for predicting multiple NCDs and mortality. Both smoking and BMI should be included in lifestyle scores aiming to predict overall NCD risk and mortality for future research and recommendations.
Zuerst veröffentlicht: 24. Juli 2025
Gesehen am 17.11.2025